Checklist of Yunnan Papilionidae (Lepidoptera: Papilionoidea) with nomenclatural notes and descriptions of new subspecies - Hu, Shao-Ji; Cotton, Adam M.; Lamas, Gerardo; Duan, Kuang; Zhang, Xin (Zootaxa, 2023)
A checklist of the Papilionidae of Yunnan is presented, with nomenclatural and taxonomic changes made. In the nomenclatural section, the junior homonym Papilio bootes nigricans Rothschild, 1895 is replaced by Papilio bootes nigricauda Lamas & Cotton nom. nov., Chilasa (Cadugoides) epycides muhabbet Koçak, 2005 is synonymised with Papilio epycides camilla Rousseau-Decelle, 1947 syn. nov., Graphium cloanthus nyghmat Koçak & Kemal, 2000 is placed as a junior objective synonym syn. nov. of Graphium cloanthus clymenus (Leech, 1893), and Papilio astorion Westwood, 1842 is shown to have priority over Papilio varuna White, 1842, thus the valid species name is Atrophaneura astorion (Westwood, 1842) comb. nov. In the main checklist, five new subspecies are described: Parnassius cephalus haba Hu & Cotton ssp. nov., Lamproptera curius hsinningae Hu, Zhang & Cotton ssp. nov., Lamproptera curius yangtzeanus Hu & Cotton ssp. nov., Graphium macareus vadimi Cotton & Hu ssp. nov., and Papilio krishna benyongi Hu & Cotton ssp. nov. The First Reviser Principle under the ICZN Code is invoked to solve four taxonomic problems, and 18 names are synonymised with explanations, notably Papilio machaon venchuanus Moonen, 1984 syn. nov., which is synonymised with Papilio machaon schantungensis Eller, 1936. Byasa genestieri (Oberthür, 1918) stat. nov. is separated from Byasa latreillei (Donovan, 1826), and Papilio everesti Riley, 1927 stat. nov. and P. verityi Fruhstorfer, 1907 stat. nov. are separated from Papilio machaon Linnaeus, 1758 as species. Taxa that require further confirmation of their presence in Yunnan and those that do not occur in Yunnan are enumerated.